An Integrated Employability Model for PWDs - Mohd Isa, Mohd Faizal; Wan Mohd Noor, Wan Shakizah; Othman, Siti Zubaidah; Abd Manaf, Abdul Razak; Azizan, Norizan; Bakar, Al Azmi (2017)
The objective of this paper was to explore employment issues among persons with disabilities (PWDs) in Malaysia and to propose a comprehensive framework which explains the factors that could contribute towards enhancing participation and integration of PWDs in the workforce.To uncover these issues, input from employers, supervisors and PWDs themselves were sought through qualitative approach using semi-structured open-ended questions.The interview protocol was developed based on past literature. Pre-test was conducted for refinement and validation.An Integrated Employability Model for PWDs was proposed.Emerging factors were derived based on data collected from 417 PWDs, 29 employers and 34 supervisors throughout Peninsular Malaysia.The results also showed that among the crucial issues surrounding employability of PWDs in the workforce were related to lack of job opportunities, negative perceptions from employers and society, accessibility issues, and personal attributes of PWDs themselves.Based on the findings of the study, several suggestions and recommendations were put forward to increase participation of PWDs in the workforce.